Internet portal in the dialogical concept of modern Belarusian regional newspapers - Ivashka, Iryna A. (Journal of the Belarusian State University. Journalism, 2022)
In the context of the digitalisation of traditional media in the Belarusian media space, the portalisation of the websites of regional publications is naturally actualised. In this regard, the activity of 16 electronic resources positioning themselves as portals or having their typological features is analysed. The common and unique characteristics inherent in the portals of modern Belarusian local newspapers are revealed.